(untitled) (Journal of School Administration Research and Development, 2018)
Changing teacher preparation to establish school-university partnerships can help candidates develop teacher identities and exceptional skills by providing supportive experiences in challenging situations. Focus groups and interviews were conducted with student teachers, teachers, principals, and program directors from a school-university partnership at its inception and seven years later. Five themes emerged: 1) change from individualistic to collective perspectives, 2) family-like, emotional support, and collaboration, 3) intensive student-teacher initiation, 4) professional development and reward systems, and 5) interconnectedness and accountability to multiple persons and supervisors.